2013
DOI: 10.1371/journal.pone.0057718
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Reference Genes in Solenopsis invicta in Different Developmental Stages, Castes and Tissues

Abstract: To accurately assess gene expression levels, it is essential to normalize real-time quantitative PCR (RT-qPCR) data with suitable internal reference genes. For the red imported fire ant, Solenopsis invicta, reliable reference genes to assess the transcript expression levels of the target genes have not been previously investigated. In this study, we examined the expression levels of five candidate reference genes (rpl18, ef1-beta, act, GAPDH, and tbp) in different developmental stages, castes and tissues of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 44 publications
(53 reference statements)
8
63
0
1
Order By: Relevance
“…These genes have been widely used as internal standards for the normalization of RT-PCR and RT-qPCR data. During the last decade, many studies have revealed the instability of housekeep- ing gene expression (31,34,35), although they can also be acceptable internal standards under certain conditions. This fact is evidence that gene expression stability varies with the gene, species, tissue, and culture conditions used (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…These genes have been widely used as internal standards for the normalization of RT-PCR and RT-qPCR data. During the last decade, many studies have revealed the instability of housekeep- ing gene expression (31,34,35), although they can also be acceptable internal standards under certain conditions. This fact is evidence that gene expression stability varies with the gene, species, tissue, and culture conditions used (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that ACT expression can change in response to a variety of conditions (Ruan & Lai 2007;Zarivi et al 2015;Wrzesińska et al 2016). Thus, these traditionally used reference genes are not persistently and stably expressed in many species or different experimental treatments (Chandna 2012;Cheng et al 2013;Ma et al 2016), which emphasised the need to evaluate reference genes in A. fatua.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect results might be obtained due to misinterpretation of RNA transcription levels especially for low abundance gene transcripts [10,11]. To date, several works were developed to determine the reference gene in Insecta, which demonstrate that is impossible to find a universal reference gene able to covering all organism and conditions [11,12,13,14,15,16,17]. The choice of a gene as reference gene is not trivial and starts with the selection of candidate reference genes to be analyzed [18].…”
Section: Introductionmentioning
confidence: 99%
“…The most studied reference genes, GAPDH and 18s rRNA, are not always expressed in a constant manner. In addition, their expression can be altered depending on the organisms and their life stages [9,12]. A good strategy for selecting potential candidate reference genes is based on previous data from species relative to the studied specie due to the high degree of similarity between genomes and the expectation of a similar expression level [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation